Răspunsuri

2014-09-28T18:55:49+03:00
A) 3 - 6x + 8 = 12
- 6x = 12 - 3 - 8 
- 6x = 1
x = - 1/6
b) 60 = 12 * (3y + 2)
60 = 36y + 24
- 36y = 24 - 60
-36y = - 36
y = 36/36
y = 1
c) 1 - 24x + 12 = 1
- 24x = 1 - 1 - 12
-24x = - 12
x = 12/24
x = 1/2
d) 1605 + 12 - 4x = 2011
- 4x = 2011 - 1605 - 12
- 4x = 394
x = - 394/4
x = - 197/2
2014-09-28T18:57:38+03:00
A)3(1-2x)+8=12
3-6x+8=12
-6x+11=12
-6x=12-11
-x=1/6      ·(-1)
x=-1/6 
b)60:(3y+2)=12
12(3y+2)=60
36y+24=60
36y=60-24
y=36/36
y=1
c)1-3(8x-4)=1
1-24x+12=1
-24x=1-13
-24x=-12                  ·(-1)
x=12/24=1/2
 d)1605+4(3-x)=2011
12-4x=2011-1605
-4x=406-12
-4x=394          
·(-1)
x=-394/4=-197/2